Both the multiplicative and single-worst-injury International Classification of Diseases Injury Severity Score underperform in urban Indian hospitals. (October 2019) - Sterner, Mattias; Attergrim, Jonatan; Claeson, Alice; Kumar, Vineet; Khajanchi, Monty; Dharap, Satish; Gerdin, Martin
Introduction: Trauma accounts for 9% of all deaths worldwide, killing almost five million people annually. As India accounts for more than one million of these deaths, research on local trauma care is of great importance. A key aspect of such research is outcome comparisons between contexts. One tool to adjust these comparisons for trauma severity is the International Classification of Diseases Injury Severity Score. The aim was to assess two versions of this score in India. Methods: The data used were from the project Towards Improved Trauma Care Outcomes in India. Published survival risk ratios were used to calculate multiplicative-International Classification of Diseases Injury Severity Score and single-worst-injury-International Classification of Diseases Injury Severity Score for the 200 most recent non-surviving patients and the surviving patients during the same period. Score performance was measured in discrimination and calibration. Results: The 30-day prediction single-worst-injury-International Classification of Diseases Injury Severity Score discriminated best with an area under the receiver operating characteristics curve of 0.668 (95% CI 0.645–0.690) and a calibration slope of 0.830 (95% CI 0.708–0.940). Conclusions: The single-worst-injury-International Classification of Diseases Injury Severity Score applied on 30-day mortality was the only score to calibrate on a satisfactory level. None of the scores had an acceptable discrimination. In interpreting these findings, we see that none of the tested scores can currently be implemented in the studied hospitals.